Analysis of Income and Welfare Level of Rice Farming Household in Ambarawa District of Pringsewu - Novianah, Okti; Murniati, Ktut; Saleh, Yuliana (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
The purpose aims to analyze rice farmer household income, farmer household expenditure, and the level of welfare farmer household. Research location was determined deliberately, namely in Ambarawa District, Pringsewu Regency because it has the second level of productivity in Lampung Province. The sample in this study was 55 rice farmer taken using simple random sampling. Household income of IDR 40.073.326 per years. Farmer household expenses amount to IDR 13.394.945 per year for food expenses and IDR 17.524.873 per year for non food expenses. According to the classification by Sajogyo (1997), the welfare level of rice farming household is included in the prosperous category with a percentage of 96,36 %.